2016
DOI: 10.1021/acsami.6b02859
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Films of VO2 on r-Cut Sapphire Achieved by Postdeposition Etching

Abstract: The metal-insulator transition (MIT) properties of correlated oxides thin films, such as VO2, are dramatically affected by strain induced at the interface with the substrate, which usually changes with deposition thickness. For VO2 grown on r-cut sapphire, there is a minimum deposition thickness required for a significant MIT to appear, around 60 nm. We show that in these thicker films an interface layer develops, which accompanies the relaxation of film strain and enhanced electronic transition. If these inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 64 publications
(92 reference statements)
1
12
0
Order By: Relevance
“…According to the reports, this kind of shift originated from the lattice mismatch between the M‐VO 2 (020) and sapphire (0001) planes. For example, the size (25.61 Å 2 ) of the repeat unit in sapphire (0001) is smaller than that (25.97 Å 2 ) of M‐VO 2 (020) …”
Section: Resultssupporting
confidence: 86%
“…According to the reports, this kind of shift originated from the lattice mismatch between the M‐VO 2 (020) and sapphire (0001) planes. For example, the size (25.61 Å 2 ) of the repeat unit in sapphire (0001) is smaller than that (25.97 Å 2 ) of M‐VO 2 (020) …”
Section: Resultssupporting
confidence: 86%
“…By contrast, the freestanding NM was chemically released from the substrate by selective etching of sacrificial layers 18 , 19 , 21 ; these chemical lift-off methods are less destructive than physical methods. However, the harsh wet condition with a strong acid or base etchant typically leaves roughening and residue on the host substrates or released membrane after the chemical etch 23 , 24 . Recently, atomically thin perovskite oxide NM was gently released by dissolving water-soluble Sr 3 Al 2 O 6 sacrificial layers 11 , but the moisture-sensitive nature of these layers prevents long-time exposure of the sacrificial layers, which restricts practical application for heterogeneous integration of oxide NM.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium dioxide (VO 2 ) is an abundant and polymorphous compound with fascinating thermal, electrical and optical properties. [1][2][3] It has been reported that there are at least six polymorphs for VO 2 , among which the rutile VO 2 (R) 4 and monoclinic VO 2 (M) 5 phases are stable structures, while the tetragonal VO 2 (A), 6 monoclinic VO 2 (B), 7 monoclinic VO 2 (D) 8 and paramontroseite VO 2 (P) 9 are metastable phases. As we all know, VO 2 must change its resistance with temperature, and the temperature coefficient of resistance (TCR) (b ¼ (1/R)vR/vT) charactering such a change should be sufficiently high; here b is the TCR, R is the resistance and T is the temperature of VO 2 lm.…”
Section: Introductionmentioning
confidence: 99%